METHODS FOR DEVELOPING BASIC AND TOPIC-SPECIFIC COMPETENCIES IN TEACHING THE ANATOMY OF THE DIGESTIVE SYSTEM - Qoyilova Mehriniso Djurayevna; Sarvinoz Jamolova; Ruhshona Muhamadova; Adiba Ashrapova (Western European Studies, 2025)
This article analyzes the role and significance of the competency-based approach in teaching the anatomy of the digestive system. The competency-based approach helps students acquire not only theoretical knowledge but also practical skills and professional competencies. The article outlines methods for developing both general (communicative, information and communication, critical thinking, teamwork) and subject-specific (morphological, topographical, clinical, experimental) competencies. The authors justify the need for integrating clinical practice into the teaching of anatomy and advocate for an individualized approach based on modular education
Keywords: Experimental competence; media technology; integration